2013
DOI: 10.3109/01443615.2012.737052
|View full text |Cite
|
Sign up to set email alerts
|

Gender attitude to the empowerment of women: An independent right to contraceptive acceptance, choice and practice

Abstract: Multiple factors influence the acceptance, choice and utilisation of contraceptive. The objective of the study is to identify individual attitude towards the empowerment of women to an independent right to accept, choose and utilise a contraceptive method of their choice without recourse to their male partners. This is a cross sectional study of men and women of different socio-cultural background working or utilising the services of the Federal Medical Centre Gombe, Nigeria. There were 554 respondents. Only 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Overall, rates of awareness of modern contraceptives were high, ranging from 85% 33 to 98%. 18 Approval of contraceptive use and the rate of joint decision on modern contraceptive use between partners ranged from 54% to 89%, 28 and 37% to 54%, 25 respectively. The location from which women obtained contraceptives varied by study, ranging from government facilities, public and private clinics or pharmacies, local church, or family and friends.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, rates of awareness of modern contraceptives were high, ranging from 85% 33 to 98%. 18 Approval of contraceptive use and the rate of joint decision on modern contraceptive use between partners ranged from 54% to 89%, 28 and 37% to 54%, 25 respectively. The location from which women obtained contraceptives varied by study, ranging from government facilities, public and private clinics or pharmacies, local church, or family and friends.…”
Section: Resultsmentioning
confidence: 99%
“…Comprehensive sexuality education therefore “must talk about parenthood and make the link between sexuality and fatherhood more explicit” (P. 139) [21]. Many adolescent pregnancy prevention programs reinforce gender inequality by reinforcing the notion that girls are the only ones responsible for preventing an unintended pregnancy [12]. Almost nothing is known about the impact of early, unintended and unwanted pregnancy on the lives of adolescent boys [77].…”
Section: Resultsmentioning
confidence: 99%
“…The attitudes towards wife beating and attitudes towards couples’ family planning decisions were included in this study to reflect inequalities under the division of power. A recent study in southern Nigeria found that about two-thirds of their respondents did not support women having independent rights to contraceptive method choice, adoption, and use [ 33 ]. Without such rights, women were less likely to practice family planning.…”
Section: Introductionmentioning
confidence: 99%